Getting to the point: Methamphetamine injection is associated with biomarkers relevant to HIV pathogenesis. (1st August 2020) - Miller, Michelle; Lee, Ji-Young; Fulcher, Jennifer A.; Roach, Margaret E.; Dilworth, Samantha E.; Chahine, Antonio; Pallikkuth, Suresh; Fuchs, Dietmar; Pahwa, Savita; Carrico, Adam W.
Highlights: Meth injection is associated with immune dysregulation in treated HIV. Meth injectors display immune dysregulation even when compared to other meth users. Meth injectors display immune dysregulation independent of recent stimulant use. Abstract: Background: People living with HIV who use stimulants, such as methamphetamine, display greater immune dysregulation and experience faster clinical HIV progression. However, it remains unclear if the extent of immune dysregulation differs between methamphetamine users who engage in injection drug use (Meth IDU) and methamphetamine users who do not. Methods: This cross-sectional study enrolled 86 sexual minority men living with HIV who had an undetectable viral load (< 40 copies/mL) and recent, biologically confirmed methamphetamine use. Meth IDU participants were compared to methamphetamine users who did not report IDU with respect to microbial translocation, immune activation, and inflammation plasma biomarkers. Multiple linear regression models were adjusted for age, antiretroviral therapy regimen, CD4 + T-cell count, and reactive urine toxicology results (Tox+) for stimulants. Results: The Meth IDU participants were significantly more likely to be homeless and Tox + for stimulants. In adjusted analyses, those reporting Meth IDU displayed elevated plasma levels of lipopolysaccharide binding protein (LBP), soluble CD163 (sCD163), interleukin-6 (IL-6), and soluble tumor necrosis factor – alpha receptor I (sTNF-αRI). Discussion: Even among methamphetamine users with treated HIV, those who engage in Meth IDU display exacerbations in key pathophysiologic processes that are linked to faster clinical HIV progression. These findings highlight the importance of screening for Meth IDU, discussing safer injection practices, and providing linkages to needle exchanges to reduce the harms of Meth IDU. Those who are not ready, willing, or able to abstain from methamphetamine use could also derive important health benefits from avoiding Meth IDU.